Oral contraceptive use and conotruncal congenital heart disease - Mars Nashrah Abdullah; Muhammad Ali; Melda Deliana; Tina Christina L. Tobing (Indonesian Pediatric Society, 2014)
Background Congenital heart disease (CHD) represents some of the more prevalent malformations among live births and remains the leading cause of death from congenital malformations. Conotruncal anomalies comprise a diverse group of CHD involving the outflow tracts of the heart and the great vessels. Oral contraceptive exposure before pregnancy may be one of the risk factors for conotruncal CHD. Objective To evaluate the effect of oral contraceptive use before pregnancy on the risk of conotruncal CHD in children. Methods A case-control study was conducted from July 2010 until July 2011 in Haji Adam Malik Hospital, Medan. Subjects with CHD were divided into two groups: conotruncal CHD as the case group and non-conotruncal CHD as the control group. Both groups had mothers with and without histories of oral contraceptive use before pregnancy. Parents were interviewed using questionnaires. Statistical analyses were performed using Chi-square test, student’s T-test, and Mann Whitney test. Results A total of 80 subjects were eligible, with 40 subjects in each group. The percentages of subjects whose mothers used oral contraceptives were 62% of the conotruncal CHD group and 60% of the non-conotruncal CHD group (OR 0.82; 95%CI 0.33 to 1.98). The mean duration of maternal oral contraceptive use before pregnancy was 19.1 months for the case group and 18.8months for the control group (P=0.87). Conclusion In children with CHD, maternal oral contraceptive use before pregnancy does not appear to increase the risk of conotruncal CHD.